Penegakan Hukum Pidana Lingkungan Atas Pencemaran Sungai Citarum (Studi Putusan 700/Pid.B/LH/2020/PN Bdg) - Azzahra Healtiane Nuryanta; Benedikta Irene Ciptaning Putri; Anita Zulfiani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The cause of the damage and pollution of the Citarum river is the development of factory activities that produce waste from these production activities, if not processed properly it can disrupt the environmental ecosystem and cause natural pollution because the waste contains hazardous and toxic substances. Apart from causing contamination and damage to the river ecosystem, this is certainly endangering human life. Therefore, the West Java government is trying to improve the condition of the Citarum river by holding various Citarum river maintenance programs. Not only focusing on the government, the community must also be involved in repairing the Citarum river. In criminal law enforcement related to environmental issues related towaste water quality standards, emission quality standards, or disturbance quality standardsmost cases are resolved through administrative or civil channels. This law enforcement uses the principle of ultimum remedium which means that criminal law is the final case to resolve a case, or is called the final application. This writing aims to analyze the criminal law arrangements regarding the criminal act of pollution of the Citarum river and law enforcement against the criminal act of environmental pollution in the Citarum river in the form of waste disposal by reviewing Law no. 32 of 2009. This research method uses the method of juridical normative law. The results of this study are industrial waste that is not managed properly will be very detrimental to society, especially if the disposal of this waste is carried out to vital resources for the general public such as the Citarum river so that strict law enforcement is needed to provide a deterrent effect on perpetrators.